Determining Zakat Recipients Using Simple Multi Attribute Rating Technique with Analytic Hierarchy Process Eigen Preference - Muhammad Ridho Anugrah; Rafi Rasyid Parmana (IJATIS: Indonesian Journal of Applied Technology and Innovation Science, 2025)
Paying zakat for Muslims is an obligation to alleviate the burden of recipients. However, difficulties arise in determining the right individuals for zakat distribution because each type of mustahiq or zakat recipient can seem similar to one and another therefore become hard distinguish. This research aims to enhance accuracy using a Decision Support System (DSS) with criteria like Number of Dependents, Income, Occupation, Home Ownership, Marital Status, House Walls, House Floors, and House Roof. The Analytic Hierarchy Process (AHP) method simplifies unstructured problems into a hierarchy, and the Simple Multi-Attribute Rating Technique (SMART) offers flexibility in analysis. Decision outcomes are rankings with the highest scores, ordering those most deserving of zakat. Weighting results highlight Number of Dependents with the highest weight at 0.335 for determining zakat recipients. Based on ranking, alternative A1 secures the top position with a score of 0.077.